PENGARUH EARNINGS PER SHARE, NET PROFIT MARGIN, DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM - Septiawan, Taufan; Hernawati, Erna (EQUITY: Jurnal Ekonomi, Manajemen, Akuntansi, 2015)
This study was conducted to examine the effect of Earnings Per Share, Net Profit Margin, Debt to Equity Ratio toward Stock Price on manufacturing companies in Indonesia Stock Exchange during the years 2009-2012. The population consists of 36 companies and are used as a sample of 17  ompanies. Sampling technique using purposive sampling method. Data were tested by using multiple regression analysis and hypothesis test with 5% level of confidence. The research results that the variables Earnings Per Share (EPS) and Net Profit Margin (NPM) gives significantly positive effect on Stock Price. The other variables Debt to Equity Ratio is not significantly to Stock Price. We suggest for investors in Indonesia Stock Exchange that paying attention other factors that regards Stock Price because with those information they can make the best decision for their investments